Characterization of vacuum HV microdischarges at HVPTF through X-ray bremsstrahlung spectroscopy. (1st January 2022) - Kushoro, M.H.; Croci, G.; Mario, I.; Muraro, A.; Rigamonti, D.; Cancelli, S.; De Lorenzi, A.; Fincato, M.; Fontana, C.; Gobbo, R.; Grosso, G.; Lotto, L.; et al.
Abstract: The development of MITICA, the prototype for a neutral beam injector for ITER, drives the interest in investigating high HV insulation in vacuum. The High Voltage Padova Test Facility (HVPTF) is an experimental device with the aim of studying the fundamental processes leading to discharges, offering a framework to develop new diagnostics, models, and mode of operations for MITICA. For this purpose, HVPTF features a vacuum chamber containing two electrodes which can achieve an HV difference up to 800 kV. X-ray bremsstrahlung radiation produced by free charges accelerated by the HV was proven to be a promising monitoring mechanism in the past; as such, two scintillating crystals, a LYSO and a LaBr3, coupled with fast electronics were used to conduct hard X-ray spectroscopy. This work describes a newly custom-developed software tool to analyze the spectroscopy from scintillators and integrate it with the HVPTF analog data. The tool was employed to study two experimental sessions, reaching promising results in the characterization of microdischarges, especially in terms of time resolution. Detection limits imposed by pile-up and other processes were identified and addressed, finding the best range of operation of the two scintillators. The performed study opens the way for the analysis of data obtained in all 2020 and 2021 experimental campaigns, thus giving the possibility to implement future improvements in HVPTF X-ray spectroscopy.